Does Cultural Hofstede dimension "Indulgence versus Restraint" impact the Corporate Performance - Houda Qasim Aleqedat (Journal of Sustainable Community Development (JSCD), 2021)
Jordan, as an Arab country located in the Middle East, began to pay attention to change. Jordanian society began to move from an old-style state to a contemporary state. Where globalization had a significant impact on culture, either in terms of individual culture and organizational culture. On the other hand, many studies emphasized that culture through its dimensions has an important role in influencing the corporate atmosphere or corporate social responsibility, as well as affecting the financial performance of companies. Moreover, the literature indicates that cultural dimensions influence the conduct of individuals and the performance of firms. . The literature indicated that there are different dimensions of culture, including Hofstede's dimensions of culture, which are Power Distance Index; Individualism versus collectivism; Masculinity versus Femininity; Uncertainty Avoidance index; Long-versus Short- Term Orientation; Indulgence versus Restraint. This study focused on the Indulgence versus Restraint dimension, as a recent dimension, where through the literature it can be predicted the existence of a critical role for the indulgence dimension on performance. After reviewing the literature related to the Indulgence dimension, it was found that there is a shortage and almost no local studies conducted in Jordan regarding the Indulgence versus Restraint dimension. Since this dimension is new, this paper stresses the importance of more research on this subject to expand the local literature on Indulgence and its impact on the performance in the Jordan context and compare it with other countries in order to provide important and useful results for the policymakers.